A hybrid membrane coating nanodrug system against gastric cancer via the VEGFR2/STAT3 signaling pathway. Issue 18 (28th April 2021) - Long, Ying; Wang, Zhou; Fan, Jialong; Yuan, Liqin; Tong, Chunyi; Zhao, Yanzhong; Liu, Bin
Abstract : This work adopted multifunctional drug CS-1 together with AP to construct a novel nanocarrier LP-R/C@AC, it enhanced drug targeting enrichment and exhibited excellent anti-gastric cancer efficiency, showing a great prospect for clinical therapy. Abstract : Although drug combination has proved to be an efficient strategy for clinic gastric cancer therapy, how to further improve their bioavailability and reduce the side effects are still challenges due to the low solubility and untargeted ability of drugs. Recently, newly emerging nanotechnology has provided an alternative for constructing new drug delivery systems with high targeting ability and solubility. In this study, a pH-responsive liposome (Liposome-PEO, LP) loaded with apatinib (AP) and cinobufagin (CS-1) was used for combinational therapy against gastric cancer after coating with a hybrid membrane (R/C). The results indicated that the constructed nanocomplex LP-R/C@AC not only efficiently killed tumor cells in vitro by inducing apoptosis, autophagy, and pyroptosis, but also significantly inhibited tumor invasion and metastasis via the VEGFR2/STAT3 pathway. Moreover, it showed stronger anti-tumor activity in gastric cancer-bearing mouse models, as compared to the sole drugs. A naturally-derived hybrid cell membrane coating bestowed nanocomplexes with enhanced biointerfacing including prolonged circulation time and targeting ability.